Contradictory Perspectives on Academic Support: Beyond Linear Logic - Hallett, Fiona (Frontiers in Education, 2021)
This paper employs a Square of Opposition as a heuristic device in order to interrogate perspectives on academic literacy support. The Square of Opposition is used to think beyond the binaries subsumed within learner-/discipline-focussed or institutionally-/epistemologically- constrained barriers to academic literacy development. In doing so, the results of this analysis demonstrate that positions that might normally be understood as opposed in fact share common features, at least where some key concepts are concerned. In particular, two ‘contradictories’ are explored; the first of these critiques the differences and similarities between contested meaning making and knowledge dissemination and the second analyses the disjuncture between skills-focussed instruction and academic literacy as a social practice. This form of analysis offers new insights that directly speak to the ways in which we conceive, and enact, personal tutoring and academic advising.